PENGEMBANGAN E-MODUL BERBANTUAN APLIKASI HEYZINE FLIPBOOK PADA MATERI PERUBAHAN ENERGI DI SEKITAR KITA - M Ryandra M Ryandra Arief putra; Yuyun Elizabeth Patras; Dadang Jaenudin (STKIP Subang, 2026)
This research used the Research and Development (R&D) method with the ADDIEdevelopment model (Analysis, Design, Development, Implementation, Evaluation).Data was collected through validation questionnaires, response questionnaires,trial tests, and pretest and posttest. Feasibility analysis was obtained throughmedia validation assessment, language validation, and material validation, as wellas product use responses from students and teachers. Product effectivenessanalysis included validity testing, reliability testing, difficulty level, discriminatingpower, and N-Gain. The results showed that the product was feasible based onmedia expert validation (100%), language expert validation (97%), material expertvalidation (100%), an average student response questionnaire of 86%, and ateacher response questionnaire of 94%. Out of 20 test items, 15 were declaredvalid, with very high reliability. The difficulty level obtained an average of 0.68(medium) and the discriminating power was 0.60 (good). Effectiveness wasmeasured using N-Gain with a result of 0.25 (low), from a pretest score of 52 to aposttest score of 64, which indicates a positive increase though not yet significant.In conclusion, the development of an e-module assisted by the Heyzine Flipbookapplication on the topic of energy changes around us was declared feasible witheffective test items, but showed low effectiveness in learning outcomes. It isrecommended that future developers pay attention to the constraints encounteredduring the research.